Idaaratu al Wahdah al Namthiyah li at Tathwiri al Tarbiyah al Islamiyah - Danusiri, Ahmad (Nadwa: Jurnal Pendidikan Islam, 2016)
Islam, through the Quran proclaims that its mission includes the teachings to the whole universe, Everything in the universe is maintained by Islam, and none of the symptoms is ignored. The revelations also include the traditions of the Prophet that are authentic (shahih) and good (hasan) in quality. Both the Quran and maqbulah hadiths are accepted by Muslims on the basis of faith. When some experts of UIN Walisongo from various disciplines try to understand the sacred words of these two resources, their understanding continues, reaching the paradigm of unity of science which essentially unites the the normative, social, and natural sciences.The effect of this paradigm has brought up an issue for the author. Is there any hadiths orÂ  Prophetic traditions that can be used as a grand theory in the management disciplines of Islamic educatio .To address this issue, the authors conducted a literature research with the title Development of Islamic Education Management Module. Sources of data were focused on nine books of Hadiths : Sahih al-Bukhari, Sahih al-Muslim, Sunan Abu Dawud, Sunan at-Turmudzi, Sunan an-Nasai, Sunan Ibn Majah, Sunan ad-Darimi, Muwatta Malik, and Musnad Imam Ahmad bin Hanbal in the form of digital dataÂ  Lidwa Reader i Software Book 9 Imam Hadith.The findings of the study stated that the meaning of the word Rabb includes: creating, nurturing, maintaining, teaching, educating, and organizing. Thus, in an academic term, the word Rabb implies a manager or leader. Meanwhile, in the concept of comprehensive manager it contains at least 14 nomenclature denotations: planning, responsibility, organization, coordination, system of employee payroll, learning, resources, humanity, principle of making it easier for the manager to the employee, motivated to achieve optimal performance, preventing unproductivity, education participation, institutional costs, monitoring and evaluation system. Each nomenclature has numerous hadiths that could serve as its grand theory. Thus, building elements of Islamic education management science have references of Prophet Muhammad SAW hadits so the final figure that was found was "prophetic educational management.